Cytotoxicity testing of chitosan derivatives on primary cultured fibroblast - Nurul Firdaus, Abdul Hadi (Universiti Sains Malaysia, 2006)
Cbitosan has been used in several studies as wound healing accelerator. This study was designed to determine the cytotoxicity of cbitosan on primary cultured human fibroblasts. Human skins were obtained from surgical specimen of consented donor and primary cultured fibroblasts were established. The fibroblasts were incubated in the absence or presence of increasing concentrations of Oligo Chito 1% and Oligo Chito 5% for 24, 48 and 72 hours. Subsequently, MIT reagent was added and 4 hours later the purple crystals produced were dissolved in DMSO. Then, cells viability was read using ELISA plate reader. Cells viability was used as a marker for toxicity. The results showed that cell viability was dependent on concentration. The cell viability decreased when high concentrations of chitosan were used. Prolonged incubation period also caused decreased cell viability. Analysis of chitosan effects on cell culture is useful as a screening tool for their potential in vivo activity as wound healing agents.